Aplikasi Sosiodrama dan Case Study terhadap Pembentukan Sikap dalam Pencegahan Penularan HIV/AIDS Calon Tenaga Kerja Indonesia (TKI) - Ning Arti Wulandari; Erni Setiyorini (Journal of Ners and Midwifery, 2016)
Infectious diseases HIV / AIDS is a disease with a high mortality rate. Indonesia ranks first in the transmission of HIV / AIDS in Southeast Asia. The number of people living with HIV / AIDS in Blitar on January-July 2013 reached 66 people and 26 died. From that numbers, many cases contributed by the group of Indonesian blue collar workers (migrant workers) (Arif, 2013). The purpose of this study was to determine the effectiveness of sociodrama and a case study on the knowledge and attitude of prevention of transmission of HIV / AIDS .The design of the study was quasy Experiment with pretest and posttest control group with the sample of 50 people, who were divided into 25 groups of control and treatment. The sampling technique was purposive sampling techniques. The treatment group received treatment of sociodrama and case study whereas the control group getting a lecture. Both groups were measured on the knowledge and preventive attitude of transmission of HIV / AIDS. The study was conducted on May-June 2016. The data was collected using a questionnaire. The level of knowledge and attitude on the treatment and control groups increased. Different test level of knowledge between the treatment and control groups using the Mann Whitney, p = 0.016, which means that there was differences in knowledge in the treatment group and the control, whereas test different attitudes using T - Test , p = 0.739, which means there was no difference in attitude between the treatment groups and control. The results of this study were expected to be the input for the Department of Labor and the health Department of Blitar, Komisi Pemberantasan AIDS (KPA) in Blitar, PJTKI (Perusahaan Jasa Tenaga Kerja Indonesia).